Abdomen Radiography with Atresia Ani Specifications at Bhayangkara Hospital Medan - Ariyanti, Stephanie; Sihotang, Sri Nanda (International Journal of Public Health Excellence (IJPHE), 2023)
Abdominal plain radiology examination Anal atresia aims to obtain a radiographic picture of congenital abnormalities in the anus which cause the anus to form imperfectly. The projections carried out in this radiological examination are Antero-Posterior Supine (AP), and Lateral Knee Chest (L) projections. This research uses descriptive research. Atresia ani radiology examination research time This was carried out in May-J 2021 at Bhayangkara Hospital, Medan. The X-ray aircraft used in this examination is a conventional Toshiba-DK Medical System brand aircraft with a capacity of 20 0 Kv and a maximum mA of 300 mA. Radiographic image processing uses CR (Computed Radiography). The cassette used during this examination was a CR cassette measuring 35 cm x 35 cm. The results of the research obtained from an abdominal examination with the suspicion of Atresia ani with the results of the interpretation from the radiologist being correct Atresia ani with the distance of the most distal intestinal air to the anal dimple (marker) being ± 2.6 cm.